The impact of metal dopants on the properties of nZVI: a theoretical study - Jessica Jein White; Jack Jon Hinsch; William W Bennett; Yun Wang (JPhys Materials, 2024)
The substitution of Fe with metal dopants shows potential for enhancing the wastewater remediation performance of nanoscale zero-valent iron (nZVI). However, the specific roles and impacts of these dopants remain unclear. To address this knowledge gap, we employed density functional theory (DFT) to investigate metal-doped nZVI on stepped surfaces. Four widely used metal dopants (Ag, Cu, Ni, and Pd) were investigated by replacing Fe atoms at the edge of the stepped surface. Previous research has indicated that these Fe atoms exhibit chemical reactivity and are vulnerable to water oxidation. Our DFT calculations revealed that the replacement of Fe atoms on the edge of the stepped surface is energetically more favorable than that on the flat Fe(110) surface. Our results shed light on the effects of metal dopants on the surface properties of nZVI. Notably, the replacement of Fe atoms with a metal dopant generally led to weaker molecular and dissociated water adsorption across all systems. The results from this study enhance our understanding of the complex interplay between dopants and the surface properties of nZVI, offering theoretical guidance for the development and optimization of metal-doped nZVI for efficient and sustainable wastewater remediation applications.